The Belgium and current world problems : official statements on Belgium's position with regard to the future of Europe, the integration of Europe, the North Atlantic Treaty Organization, Germany, the European army, the Schuman Plan, peace and the United Nations. (New York : Belgian Government Information Center, 1953)
Bibliotheek Camille Huysmans
Dedicator: Goris, Jan-Albert, dedicatee: Huysmans, Camille
Engels
Brochure
Keywords: internationale politiek; België